Identificando e superando dificuldades na relação cognitiva entre técnico e produtor rural: uma abordagem baseada na “biologia do conhecer" - Identifying and overcoming difficulties in the cognitive relation between technical and rural producer: an approa - Silva, Antonio Waldimir Leopoldino da (Extensão Rural, 2014)
http://dx.doi.org/10.5902/231817968170 A adequada transmissão de conhecimentos técnico-científicos ao produtor rural constitui um dos fatores determinantes do êxito da atividade agropecuária. Este artigo visa analisar a relação cognitiva existente entre técnico e produtor rural, tendo, como pano de fundo, a Biologia do Conhecer, concepção desenvolvida pelos cientistas Humberto Maturana e Francisco Varela. São apresentadas as dificuldades e barreiras que fazem com que o conhecimento técnico não chegue ao produtor ou não seja adequadamente assimilado e empregado. Faz-se necessário que o saber do assistente técnico ou extensionista rural dialogue com o conhecimento local, ou seja, o técnico deve desempenhar o papel de educador-educando e o produtor, o de educando-educador. Sendo gerado em um processo que se retroalimenta, o conhecimento assume a dimensão autopoiética, porque produz a si mesmo e produz novos saberes. Reforça-se a importância de elementos como diálogo, cooperação, comprometimento, aceitação e respeito mútuo entre os atores. Palavras-chave: conhecimento local, conhecimento científico, extensão rural, Maturana e Varela, produtor rural. Identifying and overcoming difficulties in the cognitive relation between technical and rural producer: an approach based on "know biology" Abstract The adequate transmission of technical and scientific knowledge to rural producer is one of the factors determining the success of agricultural activity. This article aims to analyze the cognitive relationship between technician and rural producer, having as a backdrop the “Biology of Knowing”, conception developed by the scientists Humberto Maturana and Francisco Varela. The paper presents the difficulties and barriers which prevent the technical knowledge from reaching the producer, or which prevent it from being properly assimilated and employed. It is necessary that the knowledge of the technical assistant or rural extensionist dialogues with local knowledge, i.e., the technician must play the role of educator-learner and the farmer, on his turn, must play the role of learner-educator. Being generated in a process that provides feedback, the knowledge takes on the autopoietic dimension, because it produces itself and produces new knowledge. The importance of elements such as dialogue, cooperation, commitment, acceptance and mutual respect among actors is reinforced. Key words: local knowledge, Maturana and Varela, rural extension, rural producer, scientific knowledge.